2021
DOI: 10.1063/5.0037336
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning-based concept for high throughput image flow cytometry

Abstract: We propose a flow cytometry concept that combines a spatial optical modulation scheme and deep learning for lensless cell imaging. Inspired by auto-encoder techniques, an artificial neural network mimics the optical transfer function of a particular microscope and camera for certain types of cells once trained and reconstructs microscope images from simple waveforms that are generated by cells in microfluidic flow. This eventually enables the label-free detection of cells at high throughput while simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Deviations from the equilibrium RBC distributions have previously been used to assess changes in RBC flow behavior in patients with neuroacanthocytosis syndrome and COVID-19, as well as in patients before and after undergoing hemodiafiltration dialysis [34,35]. Moreover, RBC shapes in microfluidic capillary flow have been studied for healthy and diseased RBCs using manual and machine learning shape classification approaches [12,[36][37][38][39][40]. Recent studies have shown the potential of microfluidic characterizations of RBC shapes as biomarkers for specific pathologies, to assess the cell deformability [34,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Deviations from the equilibrium RBC distributions have previously been used to assess changes in RBC flow behavior in patients with neuroacanthocytosis syndrome and COVID-19, as well as in patients before and after undergoing hemodiafiltration dialysis [34,35]. Moreover, RBC shapes in microfluidic capillary flow have been studied for healthy and diseased RBCs using manual and machine learning shape classification approaches [12,[36][37][38][39][40]. Recent studies have shown the potential of microfluidic characterizations of RBC shapes as biomarkers for specific pathologies, to assess the cell deformability [34,41,42].…”
Section: Introductionmentioning
confidence: 99%